2012
DOI: 10.1021/mp200611d
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Delivery of Hydrophobin-Functionalized Porous Silicon Nanoparticles: Stability, Plasma Protein Adsorption and Biodistribution

Abstract: Rapid immune recognition and subsequent elimination from the circulation hampers the use of many nanomaterials as carriers to targeted drug delivery and controlled release in the intravenous route. Here, we report the effect of a functional self-assembled protein coating on the intravenous biodistribution of (18)F-labeled thermally hydrocarbonized porous silicon (THCPSi) nanoparticles in rats. (18)F-Radiolabeling enables the sensitive and easy quantification of nanoparticles in tissues using radiometric method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(100 citation statements)
references
References 52 publications
3
94
3
Order By: Relevance
“…46 Apolipoproteins have been also reported to bind to many types of nanoparticles, such as, titanium dioxide, silicon dioxide, zinc oxide, iron oxide, hydrocarbonized porous silicon, and polymer nanoparticles. 15,18,30,46 Taken together, plasma protein coronas appear to form in a particle size-dependent manner, and this may affect the transport and delivery of CaCO 3 to target organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Apolipoproteins have been also reported to bind to many types of nanoparticles, such as, titanium dioxide, silicon dioxide, zinc oxide, iron oxide, hydrocarbonized porous silicon, and polymer nanoparticles. 15,18,30,46 Taken together, plasma protein coronas appear to form in a particle size-dependent manner, and this may affect the transport and delivery of CaCO 3 to target organs.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, the oral Other plasma proteins, like albumin, have been reported to play a role in preventing the opsonization process and to increase particle circulation times. 15 Furthermore, some apolipoproteins can mediate the transcytosis of nanoparticles across the blood-brain barrier. 16 Hence, interactions between nanoparticles and plasma proteins or blood components potentially influence nanoparticle uptake, absorption, biodistribution, and clearance.…”
Section: Introductionmentioning
confidence: 99%
“…Surface analysis showed that the hydrophobin layer stays intact during several hours of exposure to solutions of secondary proteins without any detectable exchange with these proteins. Coating with HFBII resulted in a pronounced change in the degree of plasma protein adsorption to thermally hydrocarbonized porous silicon (THCPSi) nanoparticles (Sarparanta et al 2012). Identification of the adsorbed proteins revealed that certain opsonins and apolipoproteins are enriched in HFBII-functionalized nanoparticles, whereas the adsorption of abundant plasma components such as serum albumin and fibrinogen was decreased.…”
Section: Antifoulingmentioning
confidence: 99%
“…Up to date, many materials, eg, liposomes, block copolymers, dendrimers, and various inorganic nanomaterials, have been utilized as drug carriers in DDS. [3][4][5][6] Among them, mesoporous silica nanoparticles (MSNs) have attracted more and more attention as a promising component, [7][8][9][10][11][12][13] they are excellent candidates for many biomedical applications owing to their high specific surface area, large pore volume, tunable pore structures and well-defined surface property for modification.…”
Section: Introductionmentioning
confidence: 99%